2006
DOI: 10.1677/joe.1.06766
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin inhibits the apoptosis of chondrocytes induced by serum starvation

Abstract: The apoptosis of chondrocytes plays an important role in endochondral bone formation and in cartilage degradation during aging and disease. Prolactin (PRL) is produced in chondrocytes and is known to promote the survival of various cell types. Here we show that articular chondrocytes from rat postpubescent and adult cartilage express the long form of the PRL receptor as revealed by immunohistochemistry of cartilage sections and by RT-PCR and Western blot analyses of the isolated chondrocytes. Furthermore, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…PRL and the PRL receptor are expressed in chondrocytes (12,13), where this hormone can promote differentiation and survival. PRL stimulates the synthesis of proteoglycans and type II collagen by bone marrow-derived chondrocytic mesenchymal cells (14), and it inhibits the apoptosis of articular chondrocytes induced by serum deprivation (13). The action of PRL on chondrocyte survival may be relevant in RA.…”
Section: Introductionmentioning
confidence: 99%
“…PRL and the PRL receptor are expressed in chondrocytes (12,13), where this hormone can promote differentiation and survival. PRL stimulates the synthesis of proteoglycans and type II collagen by bone marrow-derived chondrocytic mesenchymal cells (14), and it inhibits the apoptosis of articular chondrocytes induced by serum deprivation (13). The action of PRL on chondrocyte survival may be relevant in RA.…”
Section: Introductionmentioning
confidence: 99%
“…Coss and co-workers (2000) also showed that PRLR was widely expressed in the growth plate chondrocytes in the digits of neonatal rats. Besides the growth plate chondrocytes, PRLR expression has been reported in articular chondrocytes from both humans and rats (Ogueta et al 2002;Zermeño et al 2006). In the articular chondrocytes in vitro, PRL has been found to inhibit apoptosis induced by serum starvation (Zermeño et al 2006) and to increase type II collagen expression (Ogueta et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the growth plate chondrocytes, PRLR expression has been reported in articular chondrocytes from both humans and rats (Ogueta et al 2002;Zermeño et al 2006). In the articular chondrocytes in vitro, PRL has been found to inhibit apoptosis induced by serum starvation (Zermeño et al 2006) and to increase type II collagen expression (Ogueta et al 2002). Moreover, PRL could directly induce proliferation and chondrogenic differentiation of the human marrow-derived mesenchymal stem cells to mature chondrocytes (Ogueta et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming D5 has dopamine agonist properties, this could have detrimental consequences in various immunological diseases, injuries and cancers. • Prolactin has been reported to affect a variety of other cells including human adipocytes (Asai-Sato et al, 2006;Nilsson et al, 2005), mouse adipocytes (Flint et al, 2006) rat cholangiocytes (Bogorad et al, 2006a, b), rat chondrocytes (Zermeno et al, 2006), human natural killer (NK) cells (Sun et al, 2004), developing human thymocytes (Carreno et al, 2005), and rat pancreatic islet cells (Amaral et al, 2004).…”
Section: Other Human Health Concernsmentioning
confidence: 99%